Geological Trap Controlling the Residence Time of Groundwater in Assessment of Exploitation Zone for Its Sustainable Resources Case Study: The Slope of Karang Mount, Banten Province, Indonesia - Johanes Hutabarat; Azwar Satrya Muhammad; Teuku Yan Waliana Muda Iskandarsyah; Yudhi Listiawan; M. Ridfan Trisnadiansyah; Putu Ayu Andhira; Hendarmawan Hendarmawan (Indonesian Journal on Geoscience, 2023)
The southern slope of Mount Karang is covered by complex volcanic deposits with complicated texture and structure. The study on zone or location of water resources which would be exploited required a comprehensive hydrogeological approach. Through detailed geological mapping, spring sampling, and well drilling were carried out. Representative spring water samples were taken to be analyzed in the laboratory, and to obtain the data of physical groundwater, chemical groundwater, stable isotopes 18O (oxygen-18), and deuterium contents, as well as the age of the groundwater. In general, the groundwater facies of the studied area showed Ca, Na, KHCO3 with several sites indicating changes to CaHCO3 during the dry and rainy seasons. The synthesis results of the stable isotope 18O (oxygen-18) and deuterium contents, verified by the physical and chemical groundwater controlled by geological setting in the groundwater subbasins, show the anomaly of residence time as trapped by the normal fault in the middle of the studied area. The existing normal fault might control this anomaly of residence time of groundwater surrounding site JH1, JH9, and JH20. However, the distribution of three different water source zones occurred. All group of groundwater indicated a complex flowing with geological setting controlling the physical, chemical content, and the age of the groundwater. At last, sites JH4, JH5, and JH9 show that the zones are proper to be developed as sustainability groundwater resources. Keywords: groundwater facies, stable isotope, groundwater flow, sustainable water